ASU effect on bone repair in defects grafted with bone substitute - Pereira, Lucas de Sousa Goulart; de PAULA, Luiz Guilherme Freitas [UNESP]; Spin-Neto, Rubens; Stavropoulos, Andreas; Marcantonio, Rosemary Adriana Chiérici [UNESP]; de OLIVEIRA, Guilherme José Pimentel Lopes (My University, 2024)
Introduction: Grafted areas represent a region of lower biological quality than areas of native bone. Bioactive products can improve bone quality in grafted areas. Objective: To evaluate the effect of avocado/soybean unsaponifiables (ASU) on repair of critical-size calvarial defects (CSDs) filled with osteoconductive bone substitutes Material and method: One CCD (0.5 mm) was made in each of 84 rats. These defects were filled either with coagulum (COA), deproteinized bovine bone (DBB), or tricalcium phosphate/hydroxyapatite (TCP/HA). ASU (0.6 g/kg) or saline solution (CTR) was administered daily by gavage from 15 days before surgery until the animals were euthanized (15 or 60 days after surgery) totaling 7 animals per period/group. The composition of the tissues that filled the CSDs were analyzed by histomorphometric evaluation, while the amount of mineralized tissue was evaluated by micro–CT. Result: The bone filling in COA-ASU group was significantly higher than in the COA-CTR group (46.40 ±10.41% vs. 29.00 ± 8.81% at 15 days and 52.14 ± 6.12% vs. 42.71 ± 5.21% at 60 days) (p<0.05). There were no differences regarding the bone fill between the ASU and CTR groups in DBB and HA/TCP grafted CSDs. There were higher amount of mineralized tissues in the CSDs of the CTR groups than the ASU groups at 15 days (66.73 ± 6.70% vs. 52.25 ± 9.71% in DBB grafted CSDs and 53.16 ± 10.08% vs. 37.95 ± 4.70% in HA/TCP grafted CSDs) (p<0.05). Conclusion: ASU enhanced the bone repair in the CSDs filled with COA; however, this positive effect was not seen in DBB or HA/TCP grafted CSDs.
Efeito do ASU no reparo ósseo de defeitos enxertados com substituto ósseo
Keywords: ASU; biomaterial; bone healing; critical-sized calvarial defects; histomorphometry; micro CT